KNOWLEDGE OF GOD AS A FACTOR OF A MEDIEVAL PERSONALITY FORMATION - Кошетар, У. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Aspects of a personality formation are considered on the basis of medieval philosophers works analysis.